Nodal intensification strategy : evaluation of an analytical model in metropolitan Cape Town - Morojele, N. I. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2005.